THE IMPACT OF CYBERLOAFING ON THE EMOTIONAL WELL-BEING OF PSYCHIATRIC NURSES IN SAUDI ARABIA - Aghnar Mohammed Ali Marwah; Amira Ali Alshowkan; Emad Adel Shdaifat (LIFE: International Journal of Health and Life-Sciences, 2025)
Cyberloafing, or the use of the internet in the workplace for non-work-related purposes, is an increasingly common problem in the field of professional development. Nurses face a variety of stressors, including workload and patient conflict, which can negatively affect their emotional wellbeing. While cyberloafing may provide some temporary relief, widespread use could lead to reduced productivity and increased disease transmission. This study aims to examine the impact of cyberloafing on the nurse’s emotional wellbeing in Saudi Arabia. A cross-sectional study will be conducted among about 200 psychiatric nurses, randomly selected from mental health hospitals in Saudi Arabia using sample size equation based on the expected cyberloafing prevalence from the similar study. Data will be collected using self-reported questionnaire including demographic and professional characteristics, Cyberloafing Scale and Positive and Negative Affect Schedule - Short Form (PANAS-SF). Data will be analyzed using SPSS version 28.0. Ethical issues will be considered. The study is expected to demonstrate that moderate levels of cyberloafing may be relieving in the short term, whereas excessive use may be associated with greater distress and dissatisfaction with the job. The findings will inform workplace policies on preventing cyberloafing and emphasize the relationship between nurses’ emotional wellbeing.